Catena‐Poly[[[4‐amino‐3, 5‐bis(pyridin‐2‐yl)‐4H‐1, 2, 4‐triazole‐κ2N1, N5](dicyanamido‐κN)copper(II)]‐μ2‐dicyanamido‐κ2N:N′]: coordination polymer chains linked into a bilayer by hydrogen bonds and π–π stacking interactions. Issue 4 (15th April 2014) - Setifi, Zouaoui; Setifi, Fatima; Saadi, Mohamed; Rouag, Djamil‐Azzeddine; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> In the title compound, [Cu(C2N3)2(C12H10N6)]n or [Cu(dca)2(abpt)]n, where abpt is 4‐amino‐3, 5‐bis(pyridin‐2‐yl)‐4H‐1, 2, 4‐triazole and dca is the dicyanamide anion, the CuII centre is five‐coordinate with an approximately square‐pyramidal geometry. One of the two dicyanamide ligands is a terminal ligand, but the other one acts as a μ1, 5‐bridging ligand between pairs of CuII centres, so generating a one‐dimensional coordination polymer. A combination of N—H...N and C—H...N hydrogen bonds, augmented by π–π stacking interactions, links the coordination polymer chains into a bilayer structure. Comparisons are made with some related CuII complexes containing dca ligands and heteroaromatic co‐ligands.